On the Short-Term Impact of Pollution: The Effect of PM 2.5 on Emergency Room Visits - Evangelina Dardati; Ramiro de Elejalde; Eugenio Giolito (Institute of Labor Economics (IZA), 2021)
In this paper, we study the effect of fine particulate matter (PM 2.5) exposure on Emergency Room (ER) visits in Chile. Our identification strategy exploits daily PM 2.5 variation within a hospital-month-year combination. Unlike previous papers, our data allow us to study the impact of high levels of pollution while controlling for avoidance behavior. We find that a one standard deviation increase in PM 2.5 increases respiratory ER visits by 1.4 percent. This effect is positive for all age groups but is stronger for children (less than five years old) and the elderly (more than 65 years old). Moreover, we find that the effects are stronger in geographical areas in which the share of emissions from residential wood burning is more than 75 percent. Finally, our results are robust to instrumenting pollution using wind direction and speed and to controlling for other pollutants.
Keywords: I12; I18; Q51; Q53; 330; air pollution; PM 2.5; emergency room visits